Features of psycho-functional status in skilled women boxers - Surina-Marysheva, E. F.; Malkov, V. P.; Krivokhizhina, L. V.; Erlikh, V. V. (Journal of Physical Education and Sport, 2015)
We studied specifics of psycho-functional status in women boxers. It was revealed that psychoemotional state in women boxers features higher anxiety and more significant deviation from autogenic norm. Performance of functional systems of sensomotor reactions in women boxers largely depends on functional status of the central nervous system and psychoemotional state. Sportswomen are more sensitive and emotionally excitable that may result in lesser adaptation to impact of destabilizing factors.